Impact assessment of Striga resistant maize varieties and fertilizer use in Ghana: a panel analysis - Martey, E.; Etwire, P.M.; Assfaw Wossen, T.; Menkir, A.; Abdoulaye, Tahirou (Wiley, 2023)
This study analyzes the impact of a component of climate-smart agriculture (CSA) technology—Striga-resistant maize (SRM) varieties and mineral fertilizer—on maize yield and food security using two rounds of panel data in Ghana. The study employs a multinomial endogenous switching regression model and finds that joint adoption of SRM varieties and mineral fertilizer increased maize yield by 872 kg/ha, food consumption scores by 17, and consumption per adult equivalent unit by 38 kg/ha. The positive impact of maize yield is high among adopters of multiple CSA technologies. The result is robust to an alternative endogeneity-correcting model and the implications of the findings are discussed.